Review of Everything the Light Touches by Janice Pariat. - Arpana Gurung (Litinfinite, 2023)
This review is a reflection on the latest novel by Janice Pariat Everything The Light Touches (2023), published by Harper Collins. The book is a work of fiction that tells the stories of four characters who are times and world apart yet the narrative has intricately woven them together through myths, legends, and a beautiful bond with botany.